انموذج مقترح للحكمانية في المنظمات العامة: بالتطبيق في وزارة التعليم العالي والبحث العلمي (Journal of Accounting and Financial Studies ( JAFS ), 2020)
governance Is considered as one approach that gained the attention of many researchers in Management and politics field as one of the dominant philosophies and desired in the current period, became seen as a panacea for all diseases afflicting in particular public administrative organs in General ,This concept has been associated with concepts of reorganization Reforme besidc the administrative directed to improve the efficiency and effectiveness of the performance of such devices as reflected on the totality of features and characteristics that relate to service fulfillment needs of beneficiaries and underlying phenomenon, there was also a constituent characteristics of this concept with a significant level of attention for being linked closely linked to the process of achieving the objectives of the ovganizat ivus obsectir and to ensure their success in changing competitive environment ,this concept has many models depending on the area in which they are applied and the objective to be achieved, this research represents an attempt to see how clear perception among senior management in the Ministry of higher education and scientific research on Governance and its significance and characteristics applicable to most important theories and models, which is reflected, in turn, to strengthen the capacity of the Ministry and its configurations on survival, growth and competition, current research aims to define the concept and characteristics and significance of governance in the public organization and show the most important theories and models in the field of higher education with trying to develop Model governance education in Iraq, has adopted a current search on descriptive analytical method with the aim of identifying features of this portal from theory, and finally the search reached to some conclusions and recommendations